IDENTIFIKASI FAKTOR PENYEBAB TERJADINYA CLOGGING PADA EDUCTOR PUMP KETIKA PELAKSANAAN DEBALLASTING DI ATAS KAPAL MV. HL DANGJIN - ASHAMI, MOCH ALIF; ARIFIN, MOH. ZAENAL; PRANYOTO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
On May 15, 2024, MV. HL DANGJIN experienced deballasting issues during coal loading at Puerto Drummond Port, Colombia, due to blockage in eductor pump no.2. This condition disrupted cargo operations and posed potential cargo loss. This study aims to analyze the causes of eductor pump clogging and propose solutions. Data were collected through interviews, observations, and documentation. Fishbone diagram analysis revealed mud sediment and cargo residue buildup due to insufficient maintenance, particularly on eductor components. Corrective actions included cleaning the ballast line and eductor pump, repairing the suction gauge, and re-sounding ballast water volume. To prevent recurrence, routine maintenance and inspection of ballast components and tank conditions are recommended to ensure operational reliability and avoid delays or losses.